Novel methods of resolving daily growth patterns in giant clam (Tridacna spp.) shells. (January 2022) - Liu, Chengcheng; Zhao, Liqiang; Zhao, Nanyu; Yang, Wei; Hao, Jialong; Qu, Xiaoli; Liu, Shan; Dodson, John; Yan, Hong
Highlights: Tridacna spp. shells have clear daily growth bands. DGI of Tridacna shell can be obtained accurately using fluorescence images and Sr/Ca profiles. DGI of Tridacna shell holds great promise as potential paleoweather proxy. Abstract: Sclerochronology is a powerful tool for high resolution paleoclimate and paleoenvironment reconstruction. However, we can only observe annual growth bands using traditional technology for most marine bivalves, hampering the ability to establish daily resolution chronology in order to reconstruct past weather changes. Giant clams ( Tridacna spp.) are the largest bivalves in the world. Their hard and dense aragonite shells have clear annual and even daily growth bands, creating the potential for daily resolution chronology establishment and paleoweather reconstruction. In this study, we present two new and reliable methods that resolve daily growth patterns in giant clam shells: (1) Fluorescence image method. Measuring the width between two bright fluorescent bands of the Tridacna shell with the help of CooRecorder 9.0 software based on the clear daily growth bands obtained by laser scanning confocal microscope (LSCM). (2) Ultrahigh resolution Sr/Ca method. Counting the amount of Sr/Ca ratio data in each daily cycle derived from Tridacna shell, and then calculating the daily growth increment based on the spatial resolution of Sr/Ca data. The results show the variation of daily growth increments profiles obtained by the two methods synchronize, and the chronology uncertainty is statistically acceptable over a long-term record, indicating that both methods can estimate the daily growth increment of Tridacna shell reliably. The methods developed here lay the foundation for paleoweather reconstruction using daily growth increments of Tridacna spp.